Adaptive Islamic Student Management for Generation Z: Integrating Modern Educational Theories and Islamic Values - Dahliana, Dahliana; Almuhajir, Almuhajir (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study examines student management within Islamic educational institutions concerning Generation Z, whose digital proficiency and preference for individualized learning pose challenges to conventional, administration-centric methodologies. This research utilizes a qualitative descriptive approach via a systematic literature review to identify critical issues: decreased discipline, reduced spiritual engagement, digital distractions, and unequal access to technology. The results support a comprehensive management framework that integrates Qur’anic principles—ikhlas (sincerity), al-‘adl (justice), amanah (responsibility), syura (consultation), and rahmah (compassion)—with contemporary methodologies including data-driven decision-making, differentiated learning, and ethically oriented digital instruments (AI, LMS, gamification). This comprehensive strategy seeks to cultivate insan kamil—graduates who achieve academic excellence while maintaining moral and social integrity. The paper indicates that globalization and Indonesia's Kurikulum Merdeka present potential for innovation, although they also pose risks of injustice and value dilution in the absence of robust managerial competence and ethical alignment. The research presents a conceptual framework for competitive, value-oriented Islamic education in the digital age.